If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 3) = (4x + -5) Reorder the terms: (3 + 3x) = (4x + -5) Remove parenthesis around (3 + 3x) 3 + 3x = (4x + -5) Reorder the terms: 3 + 3x = (-5 + 4x) Remove parenthesis around (-5 + 4x) 3 + 3x = -5 + 4x Solving 3 + 3x = -5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3 + 3x + -4x = -5 + 4x + -4x Combine like terms: 3x + -4x = -1x 3 + -1x = -5 + 4x + -4x Combine like terms: 4x + -4x = 0 3 + -1x = -5 + 0 3 + -1x = -5 Add '-3' to each side of the equation. 3 + -3 + -1x = -5 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = -5 + -3 -1x = -5 + -3 Combine like terms: -5 + -3 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8
| 15(t+2)2+9t=-90 | | 2x+5(.3-2.3)=3 | | r=0.301 | | 12+6r=-4r-5-7r | | y=10*x+500 | | -5x+4-3(x-1)=-3x-(4x-1)+3 | | 13q-12q+q-2=12 | | 1.8x=.25 | | 100=x+10x | | 3x-3(4x+5)=-15 | | n-56=26 | | X^4+2x^2=6x^2 | | -13=3u-4 | | (4y+16)(4y+16)=8 | | 3-1x=6 | | 8e-4(12-5e)=60 | | 5b-6b-3=-11 | | -4(-h)=68 | | 5x-2(x-2)=-8+5x-2 | | 2f(x)=5x-7 | | 400000=x+.07x | | 30=5/6.w | | 9w-9w+w+3=15 | | x^2-12x+17.5=0 | | 5x+2y=x+4y | | -2/n=1.6/11.2 | | 3x-12x-15=15 | | M/-5=-5-18 | | 8x+12+x=180 | | 9r-5r-3r=20 | | 10=s-15 | | -3h-5=22 |